PENGEMBANGAN E-ENSIKLOPEDIA FISIKA BERBASIS WEB PADA MATERI GELOMBANG BUNYI TERINTEGRASI KEARIFAN LOKAL - Yulianuzha (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2025)
This study aims to produce a digital learning media in the form of a WEB-based Physics E-Encyclopedia that is feasible in terms of construct and content. The digital learning media developed in this study is a WEB-based Physics E-Encyclopedia application that contains sound wave material integrated with local wisdom. Local wisdom integrated into the principles of physics is traditional musical instruments originating from several regions in Indonesia. This study uses a 4D development model (Define, Design, Develop, Disseminate). The feasibility of the Physics E-Encyclopedia is measured by product validity based on the Aiken's V index. The results of the study indicate that the WEB-based Physics E-Encyclopedia containing sound wave material is feasible in terms of construct and content.